Evaluación física y fitosanitaria en la calidad productiva de las plantas de café y sus impactos ambientales generados en Moyobamba - Carrero Oblitas, Yerson Joel (2015)
This thesis project was launched in the month of August 2012, ending up .in the month of December 2014. lt was realized in Alfarillo locality, Ochane, located in Moyobamba district and province - San Martín. The specific aims were, identify the physical and phytosanitary agents of major influence in the productive quality of the coffee; to·measure the influence of the_ phytosanitary agents in the performance of coffee; coffee grower determines the environmental impacts generated by the production, in Moy_ob_amba_. Physical Agents with the highest incidence, according to the proposed $Cale of 1 to 4 identified in the field, were: The soil, water, T0 , macro and micro nutrients with the scale of degree 4 (maximum influence). The light and the highlights were 3. The stoniness, winds, clouds and effective depth, was 2. And the plant protection agents with the highest incidence according to the scale of 1 to 4 were: insects that cause damage of fruits and leaves, and the mushrooms was grade 4; the bacteria and the weeds of grade 3; and the nematodes of grade 2. To measure the influence of plant protection agents that influence the coffee quality, in the "Catimor" variety, considering the incidence of the disease, it was found that the "Aranero" presented the highest % incidence, followed by the "eye of chicken", and evaluated in five sectors coffee growers. Among the physical agents that influence the quality of the coffee fruits, in conventional systems, in the sectors assessed were the texture of the soil, the % coverage with organic debris from the ground, this as being related to the retention of the water. According to the Environmental lmpact Study (E. l. A), we found a zero impact on the sectors handled coffee with shadow and system multistrata, in addition to good mis handling of their waste generated by the processing of the coffee, the development of the mitigations, such as plantations in curves to level and with live barriers diminish the negative effects. However, the Environmental lmpact Study in the coffee plantations in full sunlight showed an average impact, being the most affected the physical and biological- environment, by agricultura! production activities coffee, this is the impact generated by anthropogenic activities, being greater the irreversible damage in areas of conservation and environmental protection, generating a very negative impact significant; mainly by impacts on the environmental elements of flora and fauna, ecological, water and soil. Key words: environmental impacts, coffee quality.